2016
DOI: 10.5897/ajb2016.15502
|View full text |Cite
|
Sign up to set email alerts
|

Natural occurrence and pathogenicity of Xanthomonas bacteria on selected plants

Abstract: The bacterial genus Xanthomonas consists of several species of economic importance, among which Xanthomonas campestris pv.musacearum (Xcm), the cause of enset and banana wilt is the most important in tropical Africa. However, the natural occurrence and host range of this species is yet to be clarified. The objectives of this study were to verify the presence of Xanthomonas bacteria on plants growing in and around enset gardens in South and Southwest Ethiopia, and to elucidate the pathogenicity of Xcm strains t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
3
8
0
Order By: Relevance
“…However, isolate I 1 was found to be a weaker pathogen as compared to other isolates. The result of the present study is in accordance with the finding of Alemayehu et al (2016), who reported that significance differences among isolates were recorded to induce initial wilting three to four weeks after inoculation under greenhouse condition. Similarly, Ibrahim (2013) reported that there was difference among Xcm isolates for inducing disease symptom on inoculated genotype.…”
Section: Wilted Robustasupporting
confidence: 82%
See 1 more Smart Citation
“…However, isolate I 1 was found to be a weaker pathogen as compared to other isolates. The result of the present study is in accordance with the finding of Alemayehu et al (2016), who reported that significance differences among isolates were recorded to induce initial wilting three to four weeks after inoculation under greenhouse condition. Similarly, Ibrahim (2013) reported that there was difference among Xcm isolates for inducing disease symptom on inoculated genotype.…”
Section: Wilted Robustasupporting
confidence: 82%
“…Yellowish bacterial ooze was observed, when pseudostem and leaf petiole were cut. Such typical symptoms were described under field and experiment condition by Gizachew (2000), Dereje (1985) and Alemayehu et al (2016).…”
Section: Evaluation Of Banana Genotype For Resistance To Xcm Pathogenmentioning
confidence: 99%
“…A more recent study by Chala et al (2016) using three Xcm isolates obtained from cultivated enset, wild enset and banana reported typical disease symptoms 2–3 weeks after the inoculations with incidences of 40–67% in maize, 25–50% in sorghum, 13% in wild sorghum and 1–17% in millet ( Eleusine coracana ). However, some of the above studies did not report re-isolation of Xcm from these alternative host plants while Koch’s postulates were not reported in all the studies.…”
Section: Introductionmentioning
confidence: 94%
“…A number of studies have been conducted to understand how other plant species (weeds and cultivated crops) in the environment of banana and enset interact with Xcm (e.g., Yirgou and Bradbury, 1974; Ashagari, 1985; Ssekiwoko et al, 2006a; Aritua et al, 2008; Karamura et al, 2015; Chala et al, 2016). Whereas studies consistently report Canna spp., a common weed, to develop XW characteristic symptoms similar to those in banana after inoculation with Xcm (Ssekiwoko et al, 2006a; Chala et al, 2016), they give a mixed and less clear picture regarding the interaction of Xcm with the cereals, especially with maize.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation